2022
DOI: 10.1590/1677-5449.202101661
|View full text |Cite
|
Sign up to set email alerts
|

Calcinose distrófica cutânea na doença venosa crônica de membros inferiores

Abstract: Resumo As úlceras de membros inferiores, secundárias à doença venosa crônica (DVC), constituem um problema significativo de saúde pública no Brasil e representam cerca de 70% do total dessas úlceras. Apesar dos recentes avanços tecnológicos e das diversas opções terapêuticas utilizadas para essas lesões crônicas, existem diversos fatores que podem estar implicados na resistência ao tratamento. A calcificação distrófica cutânea (CDC) é uma condição rara e frequentemente subdiagnosticada, que, quando associada à… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
(56 reference statements)
0
4
0
Order By: Relevance
“…1 carbonate rocks, the CaO and MgO contents came from carbonates (calcite and dolomite) whereas iron oxide came from some minerals of the mica and plagioclase group that were present in some of the processed rocks, but mainly it came from the shot and steel blades used in the sawing process. Generally, the presence of alkali metals (such as K and Na) and alkaline earth metals induce the formation of a liquid phase during ceramic firing [10,19]. Iron gives color and acts in the sintering process by reducing the viscosity of the liquid phase formed during firing, which can lead to pyroplastic deformation [12,19].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…1 carbonate rocks, the CaO and MgO contents came from carbonates (calcite and dolomite) whereas iron oxide came from some minerals of the mica and plagioclase group that were present in some of the processed rocks, but mainly it came from the shot and steel blades used in the sawing process. Generally, the presence of alkali metals (such as K and Na) and alkaline earth metals induce the formation of a liquid phase during ceramic firing [10,19]. Iron gives color and acts in the sintering process by reducing the viscosity of the liquid phase formed during firing, which can lead to pyroplastic deformation [12,19].…”
Section: Resultsmentioning
confidence: 99%
“…The residue added in the clay mixture, and the temperature and sintering time used in this work were based on the best conditions obtained in previous work, with samples containing clay and 0, 20%, 40%, 60%, and 80% of ornamental rock residue, fired at 900, 1000 and 1100 °C for 1 and 2 h [6]. Other authors [10,12,15] also indicated this firing temperature/time (1000 °C/1 h) for red ceramics due to the resulting good physical and mechanical properties. Good mechanical properties were also obtained after durability testing at 900 °C, compared to ceramics sintered at lower temperatures [16].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations